Digital Advocacy for Punitive Justice and Vigilantism: Analyzing Citizen Dissatisfaction with the Klitih Prevention Policy - Timothy Pieter Christian Siahaan; Nurhadi Susanto (Indonesian Association for Public Administration, 2023)
This study aims to investigate how the digital advocacy process in responding to the Klitih occurrence in Yogyakarta, Indonesia, was executed in expressing public dissatisfaction on social media (particularly Twitter), who are the actors, and how it will contribute to future social problem resolution. This study seeks the public response on Twitter regarding the Klitih accident that occurred in early April 2022 in Yogyakarta, Indonesia, by using the Twitter API executed in Python programming language. The analysis tools use qualitative content analysis through statistical analysis, sentiment analysis, emotional classification analysis, and social network analysis. We found that collective public responses on Twitter have successfully formed digital communities. This study observes two advocacy fibers; vigilantism and punitive law enforcement. Massive negative sentiments, colossal anger, and fear over how the Klitih issues are being resolved have a dissatisfaction impact through advocacy. The study's findings contended that the next step for digital advocacy lies in the presence of popular government opinion leaders in welcoming the advocacy and how strategies may be advanced by the dissatisfied party in lifting the advocacy to a greater stage. Future scholars can broaden it by applying the same methodology to the non- digital advocacy spectrum